SIFAT-SIFAT GRAF (2n) - L., Erly; Hariyanto, Susilo (MATEMATIKA, 2008)
A sequence of non negative integers d = (d1, d2, …, dn) is said a sequence of graphic if it is the degree sequence of a simple graph G. In this case, graph G is called realization for d. The set of all realizations of  non isomorfic 2-regular graph with order n (n ≥ 3) is denoted R(2n), whereas a graph with R(2n) as set of  their vertices is denoted (2n) . Two vertices in graph (2n)  are called adjacent if one of these vertices can be derived from the other by switching. In the present paper, we  prove that  for n ≥ 6, (2n) is a connected and bipartite graph.